2009
DOI: 10.5539/ibr.v3n1p66
|View full text |Cite
|
Sign up to set email alerts
|

Small and Medium Enterprises (SMEs) Competing in the Global Business Environment: A Case of Malaysia

Abstract: Small and Medium Enterprises (SMEs) play a vital role in the country's economic development. The current trend of economic growth and the rapid industrial development has made Malaysia as one of the most open economies in the world. In conjunction with the Ninth Malaysian Plan (2006)(2007)(2008)(2009)(2010), the government is devoting and designing the SME development plan to assist the SMEs to meet the new business challenges in the competitive global business environment. The focus of this paper is the discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 16 publications
0
59
0
4
Order By: Relevance
“…It is creating new structures and new relationships, with the result that business decisions and actions in one part of the world are having significant consequences in other places. Underlying and reinforcing these globalization trends is the rapidly changing technological environment (Muhammad et al, 2010). Increasing global competition coupled with rapidly changing technology, and shortening of product life cycles, have made corporations vulnerable to failure more than any time in the past (Jalan and Kleiner, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It is creating new structures and new relationships, with the result that business decisions and actions in one part of the world are having significant consequences in other places. Underlying and reinforcing these globalization trends is the rapidly changing technological environment (Muhammad et al, 2010). Increasing global competition coupled with rapidly changing technology, and shortening of product life cycles, have made corporations vulnerable to failure more than any time in the past (Jalan and Kleiner, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The focus is on the planning strategies of the entrepreneur. Strategies have been emphasized as very important to entrepreneurship research, particularly in the context of the growth of global markets, which stimulates competition globally and locally (Muhammad et al, 2010). Entrepreneurial actions have also been studied in pre-start-up, start-up and post-start-up phases of successful and unsuccessful enterprises.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Muhammad et al(2010) identified the main problems faced by SMEswhich could be the lack of knowledge regarding marketingtechniques, branding, customer loyalty and also lack of goodcontacts with other local and international enterprises.…”
Section: Small and Medium Enterprisesmentioning
confidence: 99%